High Proton Conductivity of 3D Graphene Oxide Intercalated with Aromatic Sulfonic Acids. Issue 4 (25th March 2022) - Atiqur Rahman, Mohammad; Islam, Md. Saidul; Fukuda, Mashahiro; Yagyu, Junya; Feng, Zhiqing; Sekine, Yoshihiro; Lindoy, Leonard F.; Ohyama, Junya; Hayami, Shinya
Abstract: The development of efficient proton conductors that are capable of high power density, sufficient mechanical strength, and reduced gas permeability is challenging. Herein, we report the development of a series of aromatic sulfonic acid/graphene oxide hybrid membranes incorporating benzene sulfonic acid (BS), naphthalene sulfonic acid (NS), naphthalene disulfonic acid (DS) or pyrene sulfonic acid (PS) using a facile freeze dried method. For out‐of‐plane proton conductivity, the 3DGO‐BS and 3DGO‐NS yielded proton conductivities of 4.4×10 −2 S cm −1 and 3.1×10 −2 S cm −1, respectively; this represents a two‐times higher value than that which occurs for three dimensional graphene oxide (3DGO). Additionally, the respective prepared films as membranes in a proton exchange membrane fuel cell (PEMFC) show maximum power density of 98.76 mW cm −2 for 3DGO‐NS while it is 92.75 mW cm −2 for 3DGO‐BS which are close to double that obtained for 3DGO (50 mW cm −2 ). Abstract : The proton conduction behavior of series of aromatic sulfonated 3DGO derivatives is reported in this work. Among these derivatives, both 3DGO‐NS and 3DGO‐BS have shown efficient proton conductivity in both in plane and out‐of‐plane directions. Moreover we have also established that 3DGO‐NS and 3DGO‐BS have shown efficient proton exchange membrane fuel cell performance.